2011
DOI: 10.3109/00365521.2011.551835
|View full text |Cite
|
Sign up to set email alerts
|

Fecal calprotectin: A selection tool for small bowel capsule endoscopy in suspected IBD with prior negative bi-directional endoscopy

Abstract: Measurement of FC levels prior to referral for SBCE is a useful tool to select patients with possible small bowel CD. A FC >100 μg/g is good predictor of positive SBCE findings, while FC >200 μg/g was associated with higher SBCE yield (65%) and confirmed CD in 50% of cases. Patients with FC between 50 and 100 μg/g had normal SBCE, despite symptoms suggestive of IBD. In all patients with clinical suspicion of CD and negative bi-directional endoscopies, FC assessment should be carried out prior to their referral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 26 publications
3
71
2
1
Order By: Relevance
“…-FC: in our center, levels of FC are determined by automated enzyme immunoassay analyzer (estimated sensitivity of 95%). The reference level for this marker in most cases is 50 µg/g but some authors have reported that the diagnostic yield of FC in SB-CD improves when this cut-off is higher (13), and this was also one of the conclusions of a previous study of our group (8). Based on this evidence, in the present study FC > 100 µg/g was considered as pathological level.…”
Section: Clinical and Laboratory Datasupporting
confidence: 76%
See 1 more Smart Citation
“…-FC: in our center, levels of FC are determined by automated enzyme immunoassay analyzer (estimated sensitivity of 95%). The reference level for this marker in most cases is 50 µg/g but some authors have reported that the diagnostic yield of FC in SB-CD improves when this cut-off is higher (13), and this was also one of the conclusions of a previous study of our group (8). Based on this evidence, in the present study FC > 100 µg/g was considered as pathological level.…”
Section: Clinical and Laboratory Datasupporting
confidence: 76%
“…Some studies have been published trying to assess the association between symptoms (7,28) or isolated biomarkers with the presence of inflammatory lesions in CE. Regarding laboratory tests, we found some case series in the literature about the usefulness of fecal markers (most of them on FC), with heterogeneous and sometimes conflicting results (8,13,29,30). There are only a few short case series analyzing the association between symptoms and biomarkers together with findings in CE.…”
Section: Discussionmentioning
confidence: 99%
“…Koulaouzidis et al 161 from Edinburgh reported results in a highly selected group of 70 patients suspected of having IBD but in whom both colonoscopy and gastroscopy had found no lesions, and in whom localised small bowel CD was suspected. No patient with calprotectin under 100 µg/g had evidence of CD on small bowel capsule endoscopy, whereas 43% (15/35) of those with calprotectin over 100 µg/g were found to have CD (mean 326 µg/g; range 116-1430 µg/g).…”
Section: Appendix 2 Search Strategymentioning
confidence: 99%
“…Finally, FC could be used as a marker for treatment assessment [32] as it decreases considerably after anti-TNF therapy, and it correlates with CD endoscopic index of severity (CDEIS) [33] as well as endoscopic mucosal healing [34]. Koulaouzidis, et al suggested that FC can direct the use of special costly investigations as capsule endoscopy which can be declined if FC level is less than 100 μg/g [35].…”
Section: Markers In Current Usementioning
confidence: 99%